2011
DOI: 10.1002/zoo.20328
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral carpal valgus deformity in hand‐reared cheetah cubs (Acinonyx jubatus)

Abstract: Four hand-reared cheetah cubs (Acinonyx jubatus) exhibited progressively severe bilateral valgus deformity of the carpi (CV) during the weaning period. Radiographs of the thoracic limbs suggested normal bone ossification, and serum chemistry was unremarkable. All affected cubs developed CV shortly after the onset of gastroenteritis, which was treated medically, and included use of a prescription diet. A sudden decrease in growth rate was associated with gastrointestinal disease. Before gastroenteritis and CV, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Relative to other felids of equivalent body size, cheetahs have small skulls, short jaws, and undeveloped canines, which are thought to be a consequence of evolutionary selection for a body design capable of high speeds [Van Valkenburgh, ; Bell, ]. Although the feeding of meat chunks to captive cheetahs may address the impaired ability of cheetahs to manipulate large bones in their diet, the practice has resulted in nutritional deficiencies when inappropriately supplemented [Christie, ; Allan et al, ; Bell et al, ]. Bechert et al [] investigated diet composition and nutritional status of cheetahs fed supplemented meat vs. commercially available raw meat diets and concluded that both diets may still result in suboptimal nutrition.…”
Section: Introductionmentioning
confidence: 99%
“…Relative to other felids of equivalent body size, cheetahs have small skulls, short jaws, and undeveloped canines, which are thought to be a consequence of evolutionary selection for a body design capable of high speeds [Van Valkenburgh, ; Bell, ]. Although the feeding of meat chunks to captive cheetahs may address the impaired ability of cheetahs to manipulate large bones in their diet, the practice has resulted in nutritional deficiencies when inappropriately supplemented [Christie, ; Allan et al, ; Bell et al, ]. Bechert et al [] investigated diet composition and nutritional status of cheetahs fed supplemented meat vs. commercially available raw meat diets and concluded that both diets may still result in suboptimal nutrition.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the important noninfectious diseases of neonatal and juvenile cheetahs are nutritionally based (Chapters 24 and 26). Bilateral carpal valgus deformities that may require surgical repair have been noted in captive cheetahs at multiple facilities (Allan et al, 2008;Bell et al, 2011). In these cases, cubs presented with lameness around 6 months of age or during weaning.…”
Section: Diseases Of Neonatal and Juvenile Cheetahsmentioning
confidence: 99%
“…Excess dietary calcium can inhibit cartilage maturation and contribute to osteochondrosis, an underlying cause of these deformities (Allan et al, 2008). In some cases, however, affected cheetahs were fed the same diet as unaffected littermates, suggesting that other factors may also be involved (Bell et al, 2011). Fractures have also been reported in some cheetahs, especially in king cheetahs, after minimal trauma, raising concerns about inappropriate dietary mineral content.…”
Section: Diseases Of Neonatal and Juvenile Cheetahsmentioning
confidence: 99%
“…Cubs can then be weaned by 6-7 weeks of age (Citino, unpublished data). Weaning at a younger age leads to less carpal valgal abnormalities, which are commonly seen in hand-reared cheetahs (Bell et al, 2011;Chapter 25).…”
Section: Hand-rearingmentioning
confidence: 99%